Strength reduction factors for structural rubbercrete - Mohammed, B.S. (Higher Education Press, 2014)
Many researches have been carried out to study the fresh and hardened properties of concrete containing crumb rubber as replacement to fine aggregate by volume, yet there is no specific guideline has been developed on the mix design of the rubbercrete. The experimental program, which has been developed and reported in this paper, is designed and executed to provide such mix design guidelines. A total of 45 concrete mixes with three different water to cement ratio (0.41, 0.57 and 0.68) were cast and tested for fresh and mechanical properties of rubbercrete such as slump, air content, unit weight, compressive strength, flexural strength, splitting tensile strength and modulus of elasticity. Influence of mix design parameters such as percentage of crumb rubber replacement, cement content, water content, fine aggregate content, and coarse aggregate content were investigated. Three levels of slump value (for conventional concrete mixes) has been selected; low, medium and high slump. In each slump level, water content was kept constant. Equations for the reduction factors (RFs) for compressive strength, flexural strength, splitting tensile strength and modulus of elasticity have been developed. These RFs can be used to design rubbercrete mixes based on the conventional mix (0 crumb rubber content) Â© 2014 Higher Education Press and Springer-Verlag Berlin Heidelberg.